Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 1-9 - Cumulative Review: 2

Answer

$t = -9, 3$

Work Step by Step

$-2(t+3)^{2} - 8 = -80$ $-2(t+3)^{2} = -80 + 8$ $-2(t+3)^{2} = -72$ $(t+3)^{2} = 36$ $t + 3 = ±\sqrt {36}$ $t = ±6 - 3$ $t = -9, 3$ Check: When $t = -9$ $-2(-9+3)^{2} - 8 \overset{?}{=} -80$ $-2(-6)^{2} - 8 \overset{?}{=} -80$ $-2(36) - 8 \overset{?}{=} -80$ $-72 - 8 \overset{?}{=} -80$ $-80\overset{?}{=} -80$ When $t = 3$ $-2(3+3)^{2} - 8 \overset{?}{=} -80$ $-2(6)^{2} - 8 \overset{?}{=} -80$ $-2(36) - 8 \overset{?}{=} -80$ $-72 - 8 \overset{?}{=} -80$ $-80\overset{?}{=} -80$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.